Ileosigmoid knotting: A case report of unique cause of acute abdomen in a Nepalese patient. (January 2022) - Subedi, Sushil Sharma; Gupta, Rakesh Kumar; Neupane, Durga; Agrawal, Sunit; Khanal, Bhawani; Jaiswal, Lokesh Shekher
Abstract: Introduction and importance: Ileosigmoid knotting is a surgical emergency. Common in Asian males, it is presented with signs and symptoms of diffuse peritonitis. Aggressive resuscitation with intravenous fluids and antibiotics followed by workup enable the patient hemodynamically stable. Explorative laparotomy followed by colo-colic anastomosis and double barrel ileostomy is curative. Case presentation: A 32-year-old-male from Nepal with a chief complain of diffuse abdominal pain for a day and signs of peritonitis presented to Emergency room. After assessing and stabilizing the patient, explorative laparotomy was performed. Ileal and sigmoid resection followed by colo-colic anastomosis and double barrel ileostomy was done. On regular follow-up, he is in his usual state of health. Discussion: The incidence of ileosigmoid knotting is reported to be about 1.6 cases per year. It is often misdiagnosed as non-specific intestinal obstruction which confers poor prognostic value to the patient. It should be identified promptly and intervened timely. Conclusion: Ileosigmoid knotting is a rare but dangerous differential of acute abdomen not to be missed. Early assessment and quick decision making is the key to provide excellent prognosis to the patient in need, provided adequate surgical skills are demonstrated. Highlights: Ileosigmoid knotting is a surgical emergency. It is common in Asian males. Patient presents with signs and symptoms of diffuse peritonitis. Explorative laparotomy should be done. Ileal and sigmoid resection followed by colo-colic anastomosis with double barrel ileostomy was performed.